Employing airborne lidar and archaeological testing to determine the role of small depressions in water management at the ancient Maya site of Yaxnohcah, Campeche, Mexico. (June 2017) - Brewer, Jeffrey L; Carr, Christopher; Dunning, Nicholas P.; Walker, Debra S.; Anaya Hernández, Armando; Peuramaki-Brown, Meaghan; Reese-Taylor, Kathryn
Abstract: High-resolution airborne lidar has been employed in the Maya lowlands to examine landscape modifications, detect architectural features, and expedite and expand upon traditional settlement surveys. Another potentially beneficial—and to-date underutilized—application of lidar is in the analysis of water management features such as small reservoirs and household storage tanks. The urban center of Yaxnohcah, located within the Central Karstic Uplands of the Yucatan Peninsula, provides an ideal test case for studying how the residents of this important Maya community managed their seasonally scarce water resources at the household scale. We employ an integrative approach combining lidar-based GIS analysis of 24 km 2 of the site area, ground verification, and excavation data from five small depressions to determine their function and the role they may have played in water management activities. Our research shows that some, but not all, small depressions proximate to residential structures functioned as either natural or human-made storage tanks and were likely an adaptive component of expanding Middle Preclassic to Classic period urbanization at the site. Thus, while lidar has revolutionized the identification of topographical features and hydrologic patterns in the landscape, a combination of ground verification and archaeological testing remains necessary to confirm and evaluate these features as potential water reservoirs. Graphical abstract: Inspection of our lidar-derived hillshade image identified a closed depression at CD-123. Excavation in the center of this depression (Operation D-4) located a decomposing floor. The decomposing floor and pottery sherds identify this closed depression as an ancient Maya water reservoir. Highlights: An approach combining lidar and archaeology to studying small depressions is proposed. The ancient Maya site of Yaxnohcah faced a seasonal scarcity of available water. Lidar analysis can assist in identifying topographical depressions. Excavation is necessary to determine a depression's water management capabilities. Household water management at Yaxnohcah emerged during the Middle Preclassic period.